Hubungan Kedisiplinan Siswa dan Perhatian Orang Tua Terhadap Prestasi Belajar Siswa Kelas V SD Negeri 1 Sumanding - Ainun Najikhah; Erik Aditia Ismaya; Fina Fakhriyah (Journal Prakarsa Paedagogia, 2022)
This study aims to determine the effect of parental discipline and attention on learning achievement of fifth grade elementary school students. This research uses ex post facto research method. The population in this study amounted to 20 elementary school students who were then used as research samples. Data collection techniques using questionnaires and documentation. Hypothesis testing uses correlation coefficient analysis (R), partial significance test (T test), aimultaneous significance test (F test), and coefficientof determination test (R2). The results of the study indicate that there is a positive and significant relationship between student discipline and parental attention to learning achievement according to the results of the regression coefficient test together (F test). Based on the calculations that have been mentioned, the value of Fcount > Ftable is 21.175 > 3.493 with a significance level of 0.000, so Ho is rejected.